Simulacra in Webtoon Virgo and The Sparkling by Anisha Nisfihani - Eva, Sandika; Merawati, Fitri (Universitas Negeri Semarang, 2024)
This study aims to identify forms of simulacra, including signs, images, and codes, in the Webtoon Virgo and The Sparkling by Anisha Nisfihani. The research applies Jean Baudrillard's simulacra theory, which explains that representations and technological simulations have replaced contemporary reality. This study employs a descriptive qualitative method with a narrative analysis approach, utilizing data in the form of text and images from the Webtoon. The analysis reveals 71 forms of simulacra, consisting of 29 signs, such as guitars and costumes, 28 codes, such as